Critical Success Factors to Improve the Adoption of Social Media in Teaching and Learning: A Case Study at a Traditional University - Murire, Obrain; Cilliers, Liezel (International Journal of Interactive Mobile Technologies (iJIM), 2019)
Mobile devices and social media tools are two emerging technologies that have positively influenced teaching and learning practices at traditional universities. Regardless of the popularity of social media, few lecturers make use of these tools for educational purposes. The objective of this paper was to identify critical success factors to improve the adoption of social media among lecturers at a traditional university in South Africa. The unified theory of acceptance and use of technology (UTAUT) was chosen as the theoretical foundation for this study. A quantitative, survey data collection method was uses to collect data. A questionnaire was distributed to all academics at the university, with a response rate of 39 %. From these, descriptive statistics were used to analyse data and the Pearson chi-square test was used to establish the association amongst different variables. The following CSFs were identified to enhance emerging technologies at traditional universities: management support; provide adequate ICT infrastructure and resources; provide sufficient training for lecturers, and introduce a champion to promote social media. The study, therefore, recommends that these four critical success factors must be considered by universities to adopt social media in teaching and learning.